Specific effects of distinct types of adverse childhood experiences on the co-occurrence of non-suicidal self-injury and suicidal behaviors among Chinese adolescents: a latent class analysis - Wang, Zhouyan; Chen, Wei; Yang, Siwei; Chen, Gen; Wan, Xiaoke; Li, Xia; Peng, Chang; Wang, Hong (Frontiers in Psychiatry, 2026)
BackgroundAdverse childhood experiences (ACEs) are well-established risk factors for both non-suicidal self-injury (NSSI) and suicidal behaviors (SBs). Actually, NSSI and SBs often co-occur among adolescents. This study aims to examine the specific effects of ACE types on the co-occurrence of NSSI and three stages of SBs in Chinese adolescents, as well as potential gender differences.MethodsA cross-sectional study was conducted in Chongqing, China. From April to May 2024. A total of 5,143 junior high school students were recruited through stratified cluster sampling. Information was collected through a self-reported questionnaire. Latent class analysis (LCA) was used to identify the co-occurrence patterns of NSSI and SBs. Multinomial logistic regression was employed to examine the independent associations between ACE types and these co-occurrence patterns. Gender differences were assessed using relative odds ratios (ROR).ResultsThe prevalence of different ACE types ranged from 2.5% to 23.0%, with 46.4% of participants reporting one or more ACEs. Three co-occurrence patterns of NSSI and SBs were identified: low risk class, suicidal ideation class, and suicide attempts class. Physical abuse (odds ratios [OR] = 1.50, 95% confidence intervals [CI] 1.05 to 2.15) was associated with suicidal ideation class, while emotional abuse (OR = 1.88, 95% CI 1.18 to 3.02) and neglect (OR = 1.45, 95% CI 1.01 to 2.09) were associated with suicide attempts class. A gender difference was found in the association between neglect and suicide attempts class (ROR = 2.34, 95% CI 1.14 to 4.83).ConclusionsSuicide attempts (SA) and suicidal ideation (SI) tend to co-occur with NSSI among adolescents. Distinct ACE types have unique effects on this co-occurrence, with gender differences. These findings emphasize the importance of considering NSSI and SBs together, and it is more promising to develop tailored anti-ACEs interventions.